Analisis Faktor-Faktor Karateristik PUS Terhadap Pemilihan Kontrasepsi Suntik Di Kelurahanan Parak Laweh - Rezi, Elma (JURNAL PENDIDIKAN KESEHATAN, 2023)
The use of injectable contraceptives compared contraception more. BKKBN 2019 based injectable contraceptive users is 47.5% more than the contraceptive pill, impalant, IUD, condoms, MOW, MOP. Based on the 2019 Padang DKK CICs more than half of which 53.2% compared to the contraceptive pill, impalant, IUD, condoms, MOW, MOP. The purpose of this study was to determine the characteristics of the analysis of the factors for the selection of injectable contraceptives EFA. This type of research is descriptive. Total population is taken in this study is the mother acceptor injecting located in the Village Parak Laweh Puskesmas Padang Begalung many as 423 people with a total sample of 81 people. Sampling technique that is proportional random sampling. Univariate data analysis. Based on the results of user studies CICs 1 month as many as 44 people (54.3%), injectable contraceptive users age are not at risk as many as 53 people (65.4%), the injectable contraceptive parity multiparas many as 48 people (59.2%). The results are expected health professionals to provide education on the use of injectable contraceptives and expected a change in mindset for participants injectable contraceptives.